LEADERSHIP IN INTERNATIONAL CONSTRUCTION PROJECTS: IMPACT ON PAKISTAN'S ECONOMIC AND DIPLOMATIC RELATIONS - Dr. Dilawar Khan; Bahadar Sher (International Journal of Contemporary Issues in Social Sciences, 2024)
Leadership in international construction projects is crucial for Pakistan's economic development and diplomatic relations. Effective leadership ensures the successful execution of large-scale infrastructure projects, such as the China-Pakistan Economic Corridor (CPEC), which are vital for enhancing trade, investment, and connectivity. Strong project leadership drives timely completion, cost efficiency, and high-quality standards, which, in turn, attract further foreign investment and economic opportunities for Pakistan. Additionally, adept leadership in these projects fosters positive diplomatic relations by positioning Pakistan as a reliable and capable partner on the global stage. This strengthens bilateral ties, particularly with key nations like China, and promotes mutual trust and cooperation. Effective leadership also navigates geopolitical complexities, aligning project goals with national interests while maintaining regional stability. Moreover, it addresses socio-political challenges by promoting sustainable development and engaging local communities, thereby ensuring the long-term success and acceptance of these projects. In essence, leadership in international construction projects is a cornerstone for Pakistan’s economic growth and diplomatic influence, driving infrastructure development and fostering robust international partnerships.